2014
DOI: 10.1002/cne.23645
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of val‐opsin isoform‐expressing cells in the brain of adult zebrafish

Abstract: In addition to vision, light information is used to regulate a range of animal physiology. Such nonimage-forming functions of light are mediated by nonvisual photoreceptors expressed in distinct neurons in the retina and the brain in most vertebrates. A nonvisual photoreceptor vertebrate ancient long opsin (VAL-opsin) possesses two functional isoforms in the zebrafish, encoded by valopa and valopb, which has received little attention. To delineate the neurochemical identities of valop cells and to test for col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Non‐mammalian vertebrates possess a wide range of intrinsically photoreceptive sites expressing members of the non‐visual opsin family (see Hankins, Davies, & Foster, ). ISH studies in the brain of zebrafish and other teleosts have revealed different neuronal populations that express opsins (Philp et al, ; Matos‐Cruz et al, ; Fischer et al, ; Nakane et al, ; Eilertsen et al, ; Hang, Kitahashi, & Parhar, ; Sato et al, ). Some of the Opn5 (neuropsin)‐expressing forebrain populations of medaka and zebrafish (Sato et al, ) are located in regions similar to those containing the post‐optic/hypothalamic opsin and/or transducin‐expressing CSF‐c neuronal populations of lampreys (García‐Fernández & Foster, ; García‐Fernández et al, ; present results).…”
Section: Discussionmentioning
confidence: 99%
“…Non‐mammalian vertebrates possess a wide range of intrinsically photoreceptive sites expressing members of the non‐visual opsin family (see Hankins, Davies, & Foster, ). ISH studies in the brain of zebrafish and other teleosts have revealed different neuronal populations that express opsins (Philp et al, ; Matos‐Cruz et al, ; Fischer et al, ; Nakane et al, ; Eilertsen et al, ; Hang, Kitahashi, & Parhar, ; Sato et al, ). Some of the Opn5 (neuropsin)‐expressing forebrain populations of medaka and zebrafish (Sato et al, ) are located in regions similar to those containing the post‐optic/hypothalamic opsin and/or transducin‐expressing CSF‐c neuronal populations of lampreys (García‐Fernández & Foster, ; García‐Fernández et al, ; present results).…”
Section: Discussionmentioning
confidence: 99%
“…), and found different neurotransmitters (GABA, serotonin) or neuropeptide (thyrotropin‐releasing hormone) in each valop cell group in the adult brain (Hang et al . ). The majority of valop cells (co‐expressing both isoforms) are located in the thalamus and minority cell groups (with single valop isoform) in the midbrain and hindbrain.…”
mentioning
confidence: 97%
“…In the zebrafish, the VAL-opsin isoforms are expressed in both the eyes and the brain [10, 11, 15], and the VAL-opsin photoreceptors in the eyes and the brain are thought to play distinct roles in zebrafish physiology [16]. Furthermore, VAL-opsinA and VAL-opsinB photoreceptors are expected to have distinct functions in the eyes [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, F0 valopa and valopb mutants exhibited a similar parental-effect phenotype in their eggs and resultant embryos. Our previous work determined the co-expression of valopa and valopb in the thalamic valop cell group within the brain, which may play a GABA-dependent modulatory role in light-dependent physiology [15, 16]. There is evidence of seasonal variation in the levels of GABA-synthesizing enzymes in the brain and GABA control on pituitary gonadotropin release in fish species [5357].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation